2012
DOI: 10.1016/j.jesp.2012.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Smiling and sad wrinkles: Age-related changes in the face and the perception of emotions and intentions

Abstract: There is a common belief that wrinkles in the aging face reflect frequently experienced emotions and hence resemble these affective displays. This implies that the wrinkles and folds in elderly faces interfere with the perception of other emotions currently experienced by the elderly as well as with the inferences perceivers draw from these expressions. Whereas there is ample research on the impact of aging on emotion recognition, almost no research has focused on how emotions expressed by the elderly are perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
71
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 14 publications
11
71
1
1
Order By: Relevance
“…Hess et al (2012) confirmed this finding with artificially created face stimuli displaying identical expressions for younger and older faces. As an exception, Ebner et al (2010) found no age difference for posed fear expressions, but for happiness, anger, sadness, disgust, and neutrality expressions.…”
Section: Influence Of the Faces' Agementioning
confidence: 79%
See 1 more Smart Citation
“…Hess et al (2012) confirmed this finding with artificially created face stimuli displaying identical expressions for younger and older faces. As an exception, Ebner et al (2010) found no age difference for posed fear expressions, but for happiness, anger, sadness, disgust, and neutrality expressions.…”
Section: Influence Of the Faces' Agementioning
confidence: 79%
“…Age differences in expressivity are unlikely to be the sole underlying mechanism, as age-of-face effects have also been found when expressivity was controlled for (Hess et al, 2012). Further, previous research rather argues against visual scan patterns as an underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Given that emotions affect the physical configuration of facial appearance through the autonomic nervous system (Ekman 1978), facial appearance may come to communicate information to observers about an individual's chronic affective experience over time (Hess et al 2012;Malatesta et al 1987). That is, people with particular dispositions (e.g., anxiety) may come to develop static facial appearances that subtly reflect their frequent but fleeting emotional states (e.g., an anxious person may come to look permanently fearful).…”
Section: Study 2bmentioning
confidence: 99%
“…For instance, the specific wrinkles are an indicator of middle and intense AU6 (intensity B or more); the intensity of these wrinkles is used to distinguish between AU6 and AU7 (see FACS manual [Ekman et al 2002]). Hess et al [2012] studied the role of age-related structural changes on the face, such as wrinkles and folds, in the nonverbal communication of sadness and happiness. According to their results, age-related wrinkles reduce the signal clarity; emotions were perceived less accurately when shown by an old face.…”
Section: Role Of Wrinkles Presentation Mode and Intensity In The Idmentioning
confidence: 99%